Soft Power and New Chinese Diplomacy in the 21st Century with Countries of the Global South: The Latin American Case (2019)
The research analyzes China's positioning process at regional and global level, and the instruments it has implemented to assume international leadership: soft power and new cultural diplomacy as part of the process of transforming its foreign policy. This policy is expressed in various roles he has played, as a conciliator in regional conflicts, as a member of multilateral instruments at a global and regional level within Asia. All of the above, in the context of the United States withdrawal from the global agenda. Which implies that China, as a power, has sought through various mechanisms to have approaches with industrialized economies such as the European Union and with emerging economies in Latin America. Therefore, in their commercial expansion project called the New Silk Road, the European Union and Latin America play an important role.